2002
DOI: 10.14214/sf.532
|View full text |Cite
|
Sign up to set email alerts
|

Leaf life span and the mobility of “non-mobile” mineral nutrients – the case of boron in conifers

Abstract: Nutrient conservation is considered important for the adaptation of plants to infertile environments. The importance of leaf life spans in controlling mean residence time of nutrients in plants has usually been analyzed in relation to nutrients that can be retranslocated within the plant. Longer leaf life spans increase the mean residence time of all mineral nutrients, but for non-mobile nutrients long leaf life spans concurrently cause concentrations in tissues to increase with leaf age, and consequently may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…Earlier investigations showed that the concentration of Ca in needles increased almost linearly at sites with high Ca level in the soil (Wyttenbach et al 1995a), whereas other results revealed its erratic behavior (Wyttenbach et al 1995b). The results of other research studies summarized by Aphalo et al (2002) showed nonlinear increase in the Ca concentration in needles of Scots pine and lodegepole pine, but almost linear increase of these elements in Norway spruce. Borer et al (2004) put forward a hypothesis that the permanent chemical sequestration of Ca is an inducible response to the excess of available Ca, but not a constitutive process, in foliage of Picea rubens.…”
Section: Linear Increase In the Elements Concentrationmentioning
confidence: 75%
See 1 more Smart Citation
“…Earlier investigations showed that the concentration of Ca in needles increased almost linearly at sites with high Ca level in the soil (Wyttenbach et al 1995a), whereas other results revealed its erratic behavior (Wyttenbach et al 1995b). The results of other research studies summarized by Aphalo et al (2002) showed nonlinear increase in the Ca concentration in needles of Scots pine and lodegepole pine, but almost linear increase of these elements in Norway spruce. Borer et al (2004) put forward a hypothesis that the permanent chemical sequestration of Ca is an inducible response to the excess of available Ca, but not a constitutive process, in foliage of Picea rubens.…”
Section: Linear Increase In the Elements Concentrationmentioning
confidence: 75%
“…These differences are well know and have influenced the selection of the sampling procedure, for monitoring purposes, needles of the equal age were analyzed (Mulgrew and Williams 2000;Stefan et al 2000), whereas differences in the content of elements between needles of a different age were analyzed and discussed in the context of the environmental pollution (Bäucker et al 2003;Rautio and Huttunen 2003;Nakatani et al 2004;Kuang et al 2007) or effects of fertilization of stands (Lehto and Mälkönen 1994;Aphalo et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The micronutrient requirements of Betula pendula Roth. seedlings have been extensively studied in a controlled environment (Göransson and McDonald 1993;Göransson 1993Göransson , 1994Göransson , 1998Göransson , 1999, but in general coniferous species, and Norway spruce in particular, have received much more attention than deciduous forest species (Madgwick et al 1990;Van Dijk and Bienfait 1993;Linder 1995;Braekke 1994;Nihlgård et al 1997;Wyttenbach and Tobler 1998;Thelin et al 1999;Schleppi et al 2000;Aphalo et al 2002). Bergmann (1992) gives the same optimum ranges of micronutrients for all deciduous forest trees, making no differentiation between species.…”
Section: Introductionmentioning
confidence: 99%
“…Apparently B accumulated in stems during the growth season, not during the autumn. Since a large pool of B is recycled through litter, the growth of trees may be limited due to a B deficiency, especially in the spring when the soil is frozen and/or when soil is B deprived (see also Aphalo et al 2002). Yet, stems contained rather substantial amounts of B that may act as mobile reserves to be utilized in spring.…”
Section: Resorption Of Nutrients From Senescing Birch Leavesmentioning
confidence: 99%
“…Now, however, it is well established that B mobility differs across plant species (Brown and Shelp 1997;Lehto et al 2004). Plants that do not retranslocate B at all, or that have a restricted B mobility, are more susceptible to B deficiency than plants able to retranslocate B from mature tissues to sink organs (Dell and Huang, 1997;Aphalo et al 2002;Liakopoulos et al 2009). …”
Section: Introductionmentioning
confidence: 99%